METHODS FOR DETERMINING THE EFFECTIVENESS OF INHIBITORS (American Journal of Technology and Applied Sciences, 2024)
The test is carried out in the following sequence. The flask is filled with 50 ml of oil with the addition of 0.02% (by weight) inhibitor and stir for 3-5 minutes. Pour the solution into a test tube and incubate for 20 minutes. Then the solution is transferred from the test tube to the flask, and the test tube is filled with 0.5 volumes of formation water from the field being studied. The remaining volume is filled with oil from the flask. The test tube is closed, and then inverted and the stopwatch is turned on, recording the flushing of the oil film over time.